APPLICATION OF PETRI NETS FOR SYSTEMS MODELING ELECTRONIC COMMERCE - Berko, A. Y.; Vysotskaya, V. A. (Radio Electronics, Computer Science, Control, 2024)
In the given article main problems of electronically commercial are analyzed. New methods for solution of discussed problems are proposed.